Examination of Turkish University Students’ Internet Addiction in Relation to Their Parental Attachment Styles and Sociodemographics - Hatice Kumcağız (SAGE Open, 2019)
The purpose of this study was to examine university students’ Internet addiction in relation to their parental attachment and sociodemographics. The participants consisted of 402 university students aged 17 to 25 years, 249 (61.9%) of whom were female and 153 (38.1%) of whom were male. The participants completed a questionnaire comprising the Parental Bonding Instrument (PBI), the Internet Addiction Test–Short Version (IAT-SV), and a personal information form. The data were analyzed using the Pearson product-moment correlation coefficient, multiple regression analysis, and one-way analysis of variance (ANOVA). The results of the one-way ANOVA suggested that students whose fathers had low educational levels were more likely to have higher Internet addiction scores than those students whose fathers had high educational levels. The results of the Pearson product-moment correlation coefficient suggested that university students’ Internet addiction scores were negatively correlated with their age, grade point average, maternal care, maternal overprotection, paternal care, and paternal overprotection. However, the results of a stepwise regression analysis suggested that the most important predictors of Internet addiction scores were maternal overprotection and paternal overprotection; the results also suggested that age, grade point average, maternal care, paternal care, and father’s educational level did not explain the additional variance in Internet addiction scores above and beyond the maternal overprotection and paternal overprotection scores.